Attitudinal, Normative, and Resource Factors Affecting Communication Scholars’ Data Sharing: A Replication Study - Xu, Jinghong (2024)
This study explores the factors affecting communication scholars’ data-sharing intentions, a critical component of reproducibility and replicability in open science. We replicate Harper and Kim’s (2018) study, which employs the theory of planned behavior to demonstrate the impacts of attitudinal, normative, and resource factors. Specifically, their original research examines data-sharing practices among psychologists, and our replication aims to reinforce their findings within the communication field. Data from a survey of Chinese communication scholars (N = 351) are analyzed using structural equation modeling. The findings indicate that perceived benefit and perceived risk significantly influence the attitudes of communication scholars towards sharing their data, positively and negatively, respectively. Additionally, attitudes, subjective norms, journal pressure, and the conditions facilitating data sharing have a significant positive impact on communication scholars’ behavioral intentions. Perceived effort inversely affects attitudes toward data sharing but does not impact behavioral intentions. This study provides a theoretical framework for understanding data-sharing intentions and behaviors in the open science movement. The role of this research as a replication study serves as a compelling demonstration of scientific inquiry. Practical suggestions, such as fostering open dialog, institutional incentives, and cooperation between different actors to increase communication scholars’ data-sharing intentions, and recommendations for carrying out replication and reproduction studies, are discussed. Finally, we judiciously reflect on the methodological limitations of our research and highlight directions for future research on open science.